Molecular biology of the DExD-box helicases DDX49 and DDX52 - Parkes, Ashley J. (2024)
The DExD-box family of helicases represents the largest family of helicases within eukaryotes and have been primarily associated with all aspects of RNA biology, including processes of mRNA synthesis, pre-mRNA processing and ribosome biogenesis. However, despite their key roles and associations with cancer and other diseases, the biochemical activity and function of many of the human forms of these helicases remain uncharacterised. Additionally, despite becoming popularly synonymous as ‘RNA helicases’, it has become clear in recent years that in addition to their canonical roles within RNA processing, many of these proteins are multi-functional and play important roles within processes of DNA repair, transcriptional regulation and viral immunity, amongst others. In this study we examine and characterise two poorly studied helicases, Probable ATP-dependent RNA helicases DDX49 and DDX52, which are both associated with several cancers and have previously identified connections within viral immunity and DNA repair, respectively. We hypothesised that both genes processed DNA substrates in addition to RNA substrates and by testing recombinant proteins within in vitro assays with several DNA substrates were successful in confirming this hypothesis, as well as identifying novel nuclease and annealing activities within DDX49 and DDX52, respectively. We also developed and optimised a CRISPR-Cas9 gene knockout system for mammalian cells and successfully generated and performed preliminary phenotyping of heterozygous U2OS cell lines. Finally, we explore and performed a comparative study of DDX49 with a potential homolog from Asgard Archaea, providing unexpected but novel insight into the biochemistry of the yeast protein Dbp8.